Widening our horizons. Issue 2 (3rd April 2019) - Fordyce, R. Ewan
ABSTRACT: The Journal of the Royal Society of New Zealand will strongly support the new directions of Royal Society Te Apārangi. The future will embrace the wide diversity of people and of knowledge. As the flagship title of the Society, the Journal will continue to serve the research community of New Zealand/Aotearoa and the nearby Pacific. As an e-publication, we have a global reach. Our 2018 Special Issue, 'Ngā Kete: The Annual Collection of Reviews', presents the research of our Fellows and Medallists. In 2019, we have expanded our editorial board to 21, to help welcome a wider range of regular manuscripts.